2022
DOI: 10.1155/2022/9247169
|View full text |Cite
|
Sign up to set email alerts
|

A De Novo Transcriptome Analysis Identifies Cold-Responsive Genes in the Seeds of Taxillus chinensis (DC.) Danser

Abstract: Taxillus chinensis (DC.) Danser, a parasitic plant of the Loranthaceae family, grows by attacking other plants. It has a long history of being used in Chinese medicine to treat multiple chronic diseases. We previously observed that T. chinensis seeds are sensitive to cold. In this study, we performed transcriptome sequencing for T. chinensis seeds treated by cold (0°C) for 0 h, 12 h, 24 h, and 36 h. TRINITY assembled 257,870 transcripts from 223,512 genes. The GC content and N50 were calculated as 42.29% and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The roles of ZAT genes have been reported in responding to cold stress and other abiotic stresses, with some members playing crucial regulatory roles in cold stress pathways [ 18 ]. Transcriptomic analyses have shown that the ZAT genes are significantly differentially expressed under cold stress in herbaceous plants, such as Vicia sativa , Nicotiana tabacum , and Brassica napus , as well as woody plants, such as Taxillus chinensis , Citrus reticulata ‘Chongyi’, and Jatropha curcas [ 19 , 20 , 21 , 22 , 23 , 24 ]. Studies on the ZAT gene family responses to cold and other stresses have extensively been reported in Arabidopsis .…”
Section: Introductionmentioning
confidence: 99%
“…The roles of ZAT genes have been reported in responding to cold stress and other abiotic stresses, with some members playing crucial regulatory roles in cold stress pathways [ 18 ]. Transcriptomic analyses have shown that the ZAT genes are significantly differentially expressed under cold stress in herbaceous plants, such as Vicia sativa , Nicotiana tabacum , and Brassica napus , as well as woody plants, such as Taxillus chinensis , Citrus reticulata ‘Chongyi’, and Jatropha curcas [ 19 , 20 , 21 , 22 , 23 , 24 ]. Studies on the ZAT gene family responses to cold and other stresses have extensively been reported in Arabidopsis .…”
Section: Introductionmentioning
confidence: 99%